Role of Catecholamine's Compounds in Anti-Inflammatory and Antioxidant of Two Plants Santolina chamaecyparissus and Launaea mucronata - Elsharkawy, Eman; Alshathely, Mona; Jaleel, Gehad Abdel (Pakistan Journal of Nutrition, 2015)
Natural products have long been a thriving source for the discovery of new drugs because of their chemical diversity. The study was designed to investigate the anti-inflammatory, antioxidant and composition of methanol extract and alkaloid fraction of two plant family asteraceae, Santolina chamaecyparissus and Launaea mucronata growing in desert habitat of North Region. The Anti-inflammatory of plant extracts using carrageenan induced paw edema (200 mg/kg) of extracts were tested, Santolina chamaecyparissus showed high inhibition after four hour. DPPH radical scavenging activity of various leaf extracts of Launaea and Santolina were tested, all the extracts showed different levels of DPPH radical scavenging activity over the range of 2-10 mg/ml concentration, the EC50 values of MeOH extracts and alkaloid fraction of Launaea and Santolina were 27.85, 30.55 25.94 and 32.22 mg/ml, respectively. The Fluoroatropine, Aspidofractinine-3-methanol and Dehydroabietic acid are the main constituents of the extracts which investigated by capillary GC and GC-MS. The role of the identified compounds in inflammatory inhibition was discussed.